“We are left to fend for ourselves”: understanding why teachers struggle to support students’ mental health - Dabrowski, Anna; Hsien, Michelle; Van Der Zant, Tamara; Ahmed, Syeda Kashfee (Frontiers in Education, 2025)
Student mental health is linked to improved learning, and there has been significant international investment in policies, practices, and programs focused on preventing and responding to mental health conditions amongst young people. Accordingly, the number of mental health and wellbeing interventions now being implemented in education settings continues to grow, despite a lack of research on teacher readiness to implement such interventions. Numerous studies have associated educator stress and burnout with increased workloads, yet the complexity of student needs, coupled with an ongoing lack of support, continue to result in high rates of educator attrition. This paper presents the findings of a recent mixed methods study of educators from schools and universities in Australia. The research approach included three key activities: (i) a systematic document review and synthesis of literature and policy documents, (ii) a validated “teacher worry” questionnaire that explores reasons for worry amongst educators, and (iii) qualitative interviews with key stakeholders, including educational psychologists, teachers, and preservice education coordinators. Correlation analysis suggests a relationship between individual sources of worry and intention to leave the profession, while thematic analysis offers insights into the experiences of educators, and their need for better support. Overall, the findings suggest that although teachers are already heavily burdened by their workload, they are increasingly subject to elevated expectations of dealing with diverse students’ needs and behaviors. The research also indicates that educators’ stress and poor mental health reduces their motivation to help students to reach academic goals.